Point‐of‐Care Lung Sonography: An Audit of 1150 Examinations. (18th April 2017) - Sferrazza Papa, Giuseppe Francesco; Mondoni, Michele; Volpicelli, Giovanni; Carlucci, Paolo; Di Marco, Fabiano; Parazzini, Elena Maria; Reali, Francesca; Pellegrino, Giulia Michela; Fracasso, Paola; Sferrazza Papa, Simone; Colombo, Livio; Centanni, Stefano
Abstract : Objectives: Point‐of‐care lung sonography has theoretical usefulness in numerous diseases; however clinical indications and the impact of this technique have not been fully investigated. We aimed to describe the current use of point‐of‐care lung sonography. Methods: A 2‐year prospective observational study was performed by pulmonologists in an Italian university hospital. Techniques, indications, consequences of lung sonography, and barriers to the examination were analyzed. Results: A total of 1150 lung sonographic examinations were performed on 951 patients. The most common indications were diagnosis and follow‐up of pleural effusion in 361 cases (31%), evaluation of lung consolidation (322 [28%]), acute heart failure (195 [17%]), guide to pleural procedures (117 [10%]), pneumothorax (54 [5%]) and acute exacerbations of chronic obstructive pulmonary disease (30 [3%]). The mean duration of the examination ± SD was 6 ± 4 minutes. The transducers most frequently used were convex (746 [65%]) and linear (161 [14%]), whereas in 205 examinations (18%), both transducers were used. According to the judgment of the caring clinician, 51% of the examinations were clinically relevant. Conclusions: Point‐of‐care lung sonography performed by pulmonologists is quick and feasible and could be widely used for different clinical indications with a potentially high clinical impact. The widespread use of this technique may have a relevant clinical impact in several indications.